Clinical management of abnormal Pap tests: differences between US and Korean guidelines - Seyeon Won; Mi Kyoung Kim; Seok Ju Seong (Journal of Pathology and Translational Medicine, 2020)
Cervical cancer has been the most common gynecological cancer in Korea but has become a preventable disease with regular screening and proper vaccination. If regular screening is provided, cervical cancer does not progress to more than carcinoma in situ, due to its comparatively long precancerous duration (years to decades). In 2012, the American Society for Colposcopy and Cervical Pathology published guidelines to aid clinicians in managing women with abnormal Papanicolaou (Pap) tests, and they soon became the standard in the United States. Not long thereafter, the Korean Society of Gynecologic Oncology and the Korean Society for Cytopathology published practical guidelines to reflect the specific situation in Korea. The detailed screening guidelines and management options in the case of abnormal Pap test results are sometimes the same and sometimes different in the United States and Korean guidelines. In this article, we summarize the differences between the United States and Korean guidelines in order to facilitate physicians’ proper management of abnormal Pap test results.